Vitamin D and Immune Response: Implications for Prostate Cancer in African Americans - Batai, Ken; Murphy, Adam B.; Nonn, Larisa; Kittles, Rick A. (Frontiers in Immunology, 2016)
Prostate cancer (PCa) is the most common cancer among men in the U.S. African American (AA) men have a higher incidence and mortality rate compared to European American (EA) men, but the cause of PCa disparities is still unclear. Epidemiologic studies have shown that vitamin D deficiency is associated with advanced stage, and higher tumor grade and mortality, while its association with overall PCa risk is inconsistent. Vitamin D deficiency is also more common in AAs than EAs, and the difference in serum vitamin D levels may help explain the PCa disparities. However, the role of vitamin D in aggressive PCa in AAs is not well explored. Studies demonstrated that the active form of vitamin D, 1,25-dihydroxyvitamin D, has anti-inflammatory effects by mediating immune-related gene expression in prostate tissue. Inflammation also plays an important role in PCa pathogenesis and progression, and expression of immune-related genes in PCa tissues differs significantly between AAs and EAs. Unfortunately, the evidence linking vitamin D and immune response in relation to PCa is still scarce. This relationship should be further explored at a genomic level in AA populations that are at high risk for vitamin D deficiency and fatal PCa.